KONSTRUKSI PEMBERITAAN FLEXING KELUARGA SEKDA RIAU DI DETIK.COM DAN RIAUONLINE.CO.ID - ', Alfisahrin; ', Ismandianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Detik.com and Riauonline.co.id are online media outlets that frequently and intensely cover flexing cases, especially the viral reporting of the flexing incident involving the family of Riau Province's Secretary of Regional Secretary SF Hriyanto. This coverage has become a topic of conversation not only in Indonesia but also internationally. The reporting has been picked up by foreign media outlets as well. In the current era of information and communication technology, the role of mass media is paramount. Online media, with its advantage of speed in delivering news, plays a significant role in accelerating and expanding the dissemination of information to the public. In mid-March 2023, the Indonesian mass media was rocked by the coverage of flexing involving the family of the Secretary of Riau Province, SF. Hariyanto. The flexing went viral after being posted on social media, and both domestic and international media outlets, such as detik.com and riauonline.co.id, quickly responded and reported on the case. The phenomenon of flexing created a unique moment for the audience and the mass media covering it, with online, electronic, and print media being highly responsive to emerging issues in society. Detik.com and riauonline.co.id showed significant differences in their approaches and intensities of coverage, with detik.com appearing more in- depth in reporting various aspects of the flexing case. This study aims to analyze how online media outlets detik.com and riauonline.co.id construct the coverage of flexing involving the family of the Secretary of Riau Province using the Zhondang Pan and Gerald M. Kosicki Framing Analysis. The adopted research paradigm is constructivist, focusing on text analysis techniques using Pan and Kosicki's framing analysis framework. This research is important to understand how mass media shapes the framing of coverage on this flexing case and its impact on public perception.